The Living Planet : A Portrait of the Earth - Attenborough, David, 1926- (London Guid Publishing, 1984)
Host David Attenborough visits the great environmental regions of the planet to examine how plants and animals adapt to their surroundings and how otherwise unrelated organisms, molded by similar conditions, develop similar techniques for solving problems of survival.
Include Color Illustration and Index
Keywords: Biology -- Life (Biology) -- Biosphere